Santidade, peregrinação e milagres no Ocidente Peninsular: a hagiografia de Santa Senhorinha de Basto (século XII) - Oliveira, Heverton Rodrigues de (2016)
Pilgrimages occupy an important role in the faith of the medieval man, as well as the miracles which had a crucial role in the religiousness of the medieval. In this regard, we survey the development of St. Senhorinha de Basto’sworship ,the flow of pilgrims who flocked at the tomb of this saint looking for a relief for a variety of diseases that ravaged them. Senhorinha de Basto (925- 982) was a religious of the monastery of St. João de Vieira, from which she had become an abbess, in the 10th century, in the northwest of the Iberian Peninsula, within the Archdiocese of Braga. In order to analyze this pilgrimage and miracles performed through the intercession of St. Senhorinha de Basto we used as a source the hagiographic report Vita Beatae Senorinae Virginis ,written in the twenty century, by a Benedictine monk of the Monastery of San Miguel de Refojos de Basto, located in northern Iberian Peninsula. Our purpose in this work will investigate stem from the hagiography Santa Senhorinha some of the medievalist religiosity features, such as the pilgrimage and the pursuit of miracles.